2014
DOI: 10.1097/hjh.0000000000000008
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed hypertension among young adults with regular primary care use

Abstract: Objective:Young adults meeting hypertension diagnostic criteria have a lower prevalence of a hypertension diagnosis than middle-aged and older adults. The purpose of this study was to compare the rates of a new hypertension diagnosis for different age groups and identify predictors of delays in the initial diagnosis among young adults who regularly use primary care.Methods:A 4-year retrospective analysis included 14 970 patients, at least 18 years old, who met clinical criteria for an initial hypertension diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 37 publications
9
84
0
3
Order By: Relevance
“…In addition, several studies described delays in hypertension diagnosis and treatment in a U.S. population not limited to patients with diabetes. 10,[33][34][35] Similar to those studies, we demonstrated that fewer primary care visits in the baseline period were associated with slower diagnosis and treatment rates, emphasizing the importance of timely hypertension follow-up.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, several studies described delays in hypertension diagnosis and treatment in a U.S. population not limited to patients with diabetes. 10,[33][34][35] Similar to those studies, we demonstrated that fewer primary care visits in the baseline period were associated with slower diagnosis and treatment rates, emphasizing the importance of timely hypertension follow-up.…”
Section: Discussionsupporting
confidence: 79%
“…If more than one blood pressure was taken at a visit, the average was used. 10 Hospital and emergency department blood pressures were excluded. Each patient meeting blood pressure eligibility and currently managed criteria received an Bindex date^(the first date both criteria were met).…”
Section: Samplementioning
confidence: 99%
“…A recent study of adults with regularly scheduled physician visits who met clinical criteria for hypertension found that those who were ages 18-24 years vs. at least 60 years of age were 28 % less likely to have their hypertension diagnosed by their physician. 10 Moreover, young adults are less likely to receive information about lifestyle changes to address hypertension. 11 Often described as the "young invincibles," 12 young adults may also not consider themselves at risk for chronic diseases such as hypertension and cardiovascular disease (CVD0.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 It is needed to use other coded information, such blood pressure measurement and antihypertensive drug prescription. However, antihypertensive drugs could be prescribed for treatment of many other conditions, such as migraine, angina, heart failure, cardiac arrhythmia, chronic kidney diseases and stroke.…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%